Perubahan Paradigma dalam Karakteristik Pribadi, Sosial, dan Ekonomi Rohaniawan Hindu (Sulinggih) di Bali - Anak Agung Ketut Ayuningsasi; I Wayan Sukadana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The life of the Hindu community in Bali cannot be separated from their religious activities and customs. The presence of Sulinggih (a Hindu priest in Bali) as the leader of the ceremony also plays an important role in religious activities in Bali. Various phenomena that occur in religious life in Bali, especially those related to Sulinggih's personal, social, and economic characteristics direct this research to examine the paradigm shift related to Sulinggih in Bali. This study aims to analyze Paradigm Changes in Personal, Social, and Economic Characteristics of Hindu Clergy (Sulinggih) in Bali. This research uses literature study and quantitative approach to describe this phenomenon. The results of this study indicate that from Sulinggih's personal characteristics in Bali, Sulinggih is currently mostly of productive age, different from those who previously generally became Sulinggih when entering retirement. From the social aspect, the changes that occur are related to the existence of various rules and prohibitions that are socially established in the community to maintain the sanctity of Sulinggih. Economically, Sulinggih's characteristics are also changing. This is related to efforts to earn income which conditions were very different in the past.